Willingness to pay more for green products: The interplay of consumer characteristics and customer participation. (November 2018) - Wei, Shuqin; Ang, Tyson; Jancenelle, Vivien E.
Abstract: The extant evidence evaluating consumers' willingness to pay more for green products has been mixed. Existing investigations stem from an overemphasis on profiling consumers who are willing vs. unwilling to pay price premiums for green products using dispositional (socio-demographic and psychological) characteristics. However, little is known about what firm-initiated actions can be taken when consumers do not possess characteristics that favorably influence green purchase behaviors. This research demonstrates that customer participation improves consumers' willingness to pay more even when consumers exhibit low sustainability-oriented motivation (environmental concern) and ability (eco-literacy). The findings are important for practitioners seeking practical ways to alleviate green purchase barriers.